Under surveillance: being watched in modern America - Lewis, Randolph (University of Texas Press, 2017)
Feeling surveillance -- Welcome to the funopticon : the insidious pleasures of ludic surveillance -- Growing up observed : surveillance and childhood -- Watching Walden : surveillance in the wild -- A mighty fortress is our god : selling surveillance in the Bible Belt -- The business of insecurity : inside the new surveillance marketplace